Evaluation Of Macroprudential Policy On Credit Growth In Indonesia: Credit Registry Data Approach - Badara Shofi Dana (ETIKONOMI, 2018)
Macro-prudential policies have an essential role in mitigating the imbalances in the financial sector that stem from procyclical credit growth. This study aims to evaluate macro-prudential policy in mitigating risk on procyclical credit growth with a registry data approach. Structural Vector Autoregression (SVAR) analysis method is used to evaluate macro-prudential policy in influencing credit growth. The results show LTV instruments can reduce credit growth but not to procyclical mitigation. Dissimilar results in the implementation of CCB and GWM + LDR instruments are capable of procyclical credit mitigation. Policies that can be done by the central bank are the establishment of an early warning system in macro-prudential policy as well as strengthening of Countercyclical Buffer (CCB), Loan to Value (LTV) instruments and Minimum Reserve Requirement + Loan Funding Ratio (GWM + LFR) in capturing systemic risks from various sources which further strengthens the assessment and surveillance.DOI:10.15408/etk.v17i2.7324